The proto-oncogene Int6 is essential for neddylation of Cul1 and Cul3 in Drosophila. - Rencus-Lazar, S.; Amir, Y.; Wu, J.; Chien, C.T.; Chamovitz, D.A.; Segal, D. (PLoS ONE, 2008)
Int6 is a proto-oncogene implicated in various types of cancer, but the mechanisms underlying its activity are not clear. Int6 encodes a subunit of the eukaryotic translation initiation factor 3, and interacts with two related complexes, the proteasome, whose activity is regulated by Int6 in S. pombe, and the COP9 signalosome. The COP9 signalosome regulates the activity of Cullin-Ring Ubiquitin Ligases via deneddylation of their cullin subunit. We report here the generation and analysis of two Drosophila mutants in Int6. The mutants are lethal demonstrating that Int6 is an essential gene. The mutant larvae accumulate high levels of non-neddylated Cul1, suggesting that Int6 is a positive regulator of cullin neddylation. Overexpression in Int6 in cell culture leads to accumulation of neddylated cullins, further supporting a positive role for Int6 in regulating neddylation. Thus Int6 and the COP9 signalosome play opposing roles in regulation of cullin neddylation.